Commodity Stocks and Equilibrium - Lachmann, L. M. (Review of Economic Studies, 1936)
Journal Article Commodity Stocks and Equilibrium Get access L. M. Lachmann L. M. Lachmann London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 3, June 1936, Pages 230–234, https://doi.org/10.2307/2967631 Published: 01 June 1936